Design and experiment of a low frequency non-contact rotary piezoelectric energy harvester excited by magnetic coupling. (1st November 2022) - Liu, Lei; He, Lipeng; Liu, Xuejin; Han, Yuhang; Sun, Baoyu; Cheng, Guangming
Abstract: In this paper, a low frequency non-contact rotary piezoelectric energy harvester excited by magnetic coupling (L-PEH) was proposed. Through the coupling between the magnet inside the rotor driven by rotating motion and the magnet on the piezoelectric plate, the process of rotating motion transforming into electrical energy was realized. The purpose of this paper was to improve the output performance of piezoelectric energy harvester at low frequency by optimizing the magnetic field conditions, so the influence of the number of magnets and the arrangement of magnets on the output performance was studied in detail. A series of theories, simulations and experiments proved that the alternative magnet arrangement (mode 1) could optimize the output performance of the L-PEH. When the arrangement of magnets was mode 1 and the number of magnets was 2, the peak-to-peak voltage of rectangular and circular piezoelectric plates was 182.5 V and 4.4 V at 250r/min. Under the above optimal parameter variables, the L-PEH could generate the maximum output power of 140.45 mW. In addition, the output power generated by the prototype could fully meet the power consumption of low-power electronic equipment such as light-emitting-diodes (LEDs). In general, by changing the number and arrangement of magnets, i.e. optimizing the magnetic field conditions, L-PEH could effectively collect rotational energy and had a good application prospect in the power supply of micro electronic equipment. Highlights: The prototype improves the energy harvesting efficiency at low frequencies. The prototype can power low-power electronic devices. The effect of changing magnetic field conditions on the performance is discussed. The optimum output power of the prototype is 140.45 mW.